The effects of orally supplemented vitamin D3 on serum 25(OH)D3 concentrations and growth of pre-weaning and nursery pigs - J R Flohr; Michael D Tokach; Steven C Henry; M L Potter; Lisa M Tokach; J P Goff; R L Horst; Jerome C Nietfeld; D M Madson; S M Ensley; J R Bergstrom; Joel M DeRouchey; et al. (Kansas Agricultural Experiment Station Research Reports, 2011)
A total of 270 pigs from 29 litters (PIC 327 × 1050, initially 2 d of age) were used in a 52-d study to determine the effects of oral vitamin D3 supplementation on growth performance, serum 25(OH)D3 concentrations, and bone mineralization of pre- and postweaning pigs. Vitamin D plays an essential role in maintaining proper Ca and P homeostasis within the body of mammals. Because most swine production occurs in environmentally controlled facilities, direct sunlight is no longer a source of vitamin D for the neonatal pig, which could impact bone growth and muscle function. Experimental treatments consisted of 3 oral dosage treatments: (1) control (1 mL peanut oil), (2) 40,000 IU vitamin D3 delivered in 1 mL peanut oil, or (3) 80,000 IU vitamin D3 delivered in 1 mL peanut oil. Pigs were initially weighed over 2 differ- ent days (d 0 or 2), allowing pigs to be placed on test 1 or 2 d after birth. Within a litter, pigs were assigned to similar-weight matched sets of 3 and were allotted to 1 of the 3 oral dosage treatments. Blood samples were collected from pigs of 29 matched sets (87 pigs total) prior to dosing, then the same matched set pigs were bled periodi- cally throughout the trial to measure 25(OH)D3 serum concentrations. All pigs were weighed again on d 10 and 20. On d 20, pigs were weaned and allotted to the nursery portion of the trial and all pigs were fed common diets from d 20 to 52 of age. Pigs were also randomly selected for necropsy on d 19 and d 35. Eighteen pigs were necropsied on d 19 (6 matched sets for a total of 6 pigs per treatment) and 12 pigs were necropsied on d 35 (6 control pigs and 6 pigs previously dosed with 80,000 IU vitamin D3). Bone and tissue samples were collected. All bone samples were analyzed for ash content and histopathology.; Swine Day, Manhattan, KS, November 17, 2011
Keywords: Swine Day; 2011; Kansas Agricultural Experiment Station contribution; no. 12-064-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1056; Swine; Nursery pig; Vitamin D; 25(OH)D3